2017
DOI: 10.1093/cercor/bhx161
|View full text |Cite
|
Sign up to set email alerts
|

A Layer-specific Corticofugal Input to the Mouse Superior Colliculus

Abstract: In the auditory cortex (AC), corticofugal projections arise from each level of the auditory system and are considered to provide feedback "loops" important to modulate the flow of ascending information. It is well established that the cortex can influence the response of neurons in the superior colliculus (SC) via descending corticofugal projections. However, little is known about the relative contribution of different pyramidal neurons to these projections in the SC. We addressed this question by taking advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…Layer 5 corticocollicular neurons are morphologically and physiologically distinct from layer 5 neurons which project intracortically (Games and Winer, 1988;Llano and Sherman, 2009;Rock and Apicella, 2015). Layer 6 corticocollicular neurons, in contrast, are nonpyramidal, regular-spiking neurons with elongated somata and thin, but densely branching dendrites (Slater et al, 2013;Zurita et al, 2018). Therefore, similar to the corticothalamic system where layer 5 and layer 6 neurons have distinct roles in modulating the thalamus (Ojima, 1994;Reichova and Sherman, 2004;Llano and Sherman, 2009;Theyel et al, 2010), there are two major types of neurons comprising the corticocollicular projection.…”
Section: Introductionmentioning
confidence: 99%
“…Layer 5 corticocollicular neurons are morphologically and physiologically distinct from layer 5 neurons which project intracortically (Games and Winer, 1988;Llano and Sherman, 2009;Rock and Apicella, 2015). Layer 6 corticocollicular neurons, in contrast, are nonpyramidal, regular-spiking neurons with elongated somata and thin, but densely branching dendrites (Slater et al, 2013;Zurita et al, 2018). Therefore, similar to the corticothalamic system where layer 5 and layer 6 neurons have distinct roles in modulating the thalamus (Ojima, 1994;Reichova and Sherman, 2004;Llano and Sherman, 2009;Theyel et al, 2010), there are two major types of neurons comprising the corticocollicular projection.…”
Section: Introductionmentioning
confidence: 99%
“…Another particularly diverse subset of ET neurons located in L6 are termed corticothalamic (CT) neurons because of their projections to thalamus (Bourassa and Deschênes, 1995;Zhang and Deschênes, 1997;Briggs and Usrey, 2008;Ueta et al, 2013;Zurita et al, 2017;Chevée et al, 2018;Hasse et al, 2018). L6 CT neurons are comprised of several distinct subpopulations with disparate sublaminar distributions (see below) that project to primary sensory thalamus, higher-order thalamic nuclei, or both (Lévesque et al, 1996;Zhang and Deschênes, 1997;Thomson, 2010;Shima et al, 2016;Chevée et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For now, it is uncertain why layer 6 neurons or layer 5 neurons are sometimes labeled with pulvinar injections, and sometimes not. However, it is worth noting that both layer 6 and layer 5 neurons in auditory cortex of mice were labeled by superior colliculus injections in a recent study (Zurita, Rock, Perkins, & Apicella, ), while previous studies found labeled neurons mainly in layer 5. Thus, projections of layer 5 and layer 6 neurons labeled by subcortical injections vary across studies of auditory cortex.…”
Section: Discussionmentioning
confidence: 90%